Islam dan Kebangsaan : Studi tentang Politik Islam masa Pergerakan Nasional di Indonesia - Nasihin, Nasihin (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
This paper describes the political Islam that is applied by the Dutch government during the National Movement and its implications to the formation of the State of Indonesia. As a government policy, political Islam is precisely be the trigger for a variety of organizations labeled Islam to realize itself as an entity of Muslims and as people bumiputera. Principal important issues raised in this paper is how Islam can become binding nationality bumiputera people in Indonesia?. Re related to social phenomena of all Islamic, from time to time, in principle, does not shift to the issue of the integrity of the Ummah and the " truth " doctrine. Therefore, a brief conclusion resulting from this paper is that, during the national movement, Islam has found the "common enemy" in the form of colonialism and the Christianization which has been legalized by the Dutch government. In this context, the policy of Political Islam is precisely turned into motivation for the creation of a unity of the ummah (read: unity, ed) In building a national image and "truth" doctrine, whichhas been a crucial struggle for Muslims. In a different context, Political Islam is very powerful precisely applied by the colonialists as an attempt to break up the unity of the ummah or people bumiputera, when Muslims and or people faced with the problem of building bumiputera state system. Islam is able to be binding unity" nationality", but Islam has not been able to be binding "state" bumiputera people.